Correlation of fecal calprotectin levels with the detection of treatable enteric pathogens in children with severe acute diarrheal disease in Botswana - Muhammad Rehan; Elspeth MacBain; M. Sharif Shajib; Margaret Mokomane; Kwana Lechiile; Tonya Arscott-Mills; Andrew P. Steenhoff; Loeto Mazhani; Cheryl Main; Marek Smieja; Waliul I. Khan; David M. Goldfarb; et al. (PLoS ONE, 2025)
Diarrheal disease is a leading cause of death among young children globally. Current guidelines recommend supportive treatment of acute diarrhea and using antimicrobials only with presence of blood in the stool. Select enteric pathogens, including Shigella, commonly cause disease in high-burden settings; targeted treatment of these pathogens could decrease morbidity and mortality. In settings with limited access to microbiological testing, practical diagnostics are needed to differentiate treatable causes of pediatric diarrhea. Evolving evidence suggests fecal calprotectin (fCal) could help differentiate viral and bacterial gastroenteritis. This study describes a post hoc analysis of stool samples prospectively collected from children hospitalized with severe acute diarrheal disease in Botswana. Specimens were characterized using multiplex PCR panels for selected enteropathogens and assayed for fCal. Stool samples from 312 participants were tested. Samples positive for Shigella had significantly higher fCal than samples positive for rotavirus. Stools that were negative for all assayed pathogens had higher fCal values than expected using standard normative values for healthy children in higher-income settings. Given the prevalence of Shigella and rotavirus infections in young children globally, fCal may be a useful aid to identify children with acute diarrhea for whom antimicrobials could provide benefit and potentially reduce growth failure and mortality.